ANALISIS KESEHATAN HUTAN REPONG DAMAR BERDASARKAN INDIKATOR PRODUKTIVITAS - Cici Doria; Rahmat Safe’i; Dian Iswandaru; Hari Kaskoyo (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
Repong damar by the community around the forest is used as an economic support in order to increase income to meet their daily needs, because repong damar can create a series of other economic activities such as harvesting, transporting from gardens to villages, storing, sorting, and trasnporting to wholesalers in the Krui market. This study aims to determine the value of the indicator parameters of productivity and health status of the Repong forest in Pekon Pahmungan, Pesisir Barat. To get this goals, the stages include: determining the number of cluster plots, establishing FHM cluster plots in repong damar, collecting and analyzing data on productivity and final forest health values. The results of this study indicate that the repong damar forest in Pekon Pahmungan, Pesisir Barat Regency has a moderate forest health value based on productivity indicators. This affects the management of community forests in the future with the main function of the forest, namely production. By knowing the value of productivity and forest health conditions, managers can make appropriate forest management decisions..